Tuning the Kinetics of Zinc‐Ion Insertion/Extraction in V2O5 by In Situ Polyaniline Intercalation Enables Improved Aqueous Zinc‐Ion Storage Performance - Liu, Sucheng; Zhu, He; Zhang, Binghao; Li, Gen; Zhu, Hekang; Ren, Yang; Geng, Hongbo; Yang, Yang; Liu, Qi; Li, Cheng Chao (Advanced materials (Weinheim), 2020)
Rechargeable zinc‐ion batteries (ZIBs) are emerging as a promising alternative for Li‐ion batteries. However, the developed cathodes suffer from sluggish Zn2+ diffusion kinetics, leading to poor rate capability and inadequate cycle life. Herein, an in situ polyaniline (PANI) intercalation strategy is developed to facilitate the Zn2+ (de)intercalation kinetics in V2O5. In this way, a remarkably enlarged interlayer distance (13.90 Å) can be constructed alternatively between the VO layers, offering expediting channels for facile Zn2+ diffusion. Importantly, the electrostatic interactions between the Zn2+ and the host O2−, which is another key factor in hindering the Zn2+ diffusion kinetics, can be effectively blocked by the unique π‐conjugated structure of PANI. As a result, the PANI‐intercalated V2O5 exhibits a stable and highly reversible electrochemical reaction during repetitive Zn2+ insertion and extraction, as demonstrated by in situ synchrotron X‐ray diffraction and Raman studies. Further first‐principles calculations clearly reveal a remarkably lowered binding energy between Zn2+ and host O2−, which explains the favorable kinetics in PANI‐intercalated V2O5. Benefitting from the above, the overall electrochemical performance of PANI‐intercalated V2O5 electrode is remarkable improved, exhibiting excellent high rate capability of 197.1 mAh g−1 at current density of 20 A g−1 with capacity retention of 97.6% over 2000 cycles. An in situ polyaniline (PANI) intercalation strategy is developed to facilitate the Zn2+ (de)intercalation kinetics in V2O5. PANI not only expands the diffusion channels for facilitating Zn2+ diffusion, but also maintains the structural stability as interlayer pillars. Especially, its unique π‐conjugated structure, serving as electron‐reservoir, simultaneously shields the electrostatic interactions between Zn2+ and V2O5 host.